PEMBUATAN MEMBRAN SILIKA DARI FLY ASH BATUBARA UNTUK PENURUNAN INTENSITAS WARNA DARI LIMBAH CAIR INDUSTRI SARUNG SAMARINDA - Pratiwi, Kartika; -, Bohari; Gunawan, Rahmat (Jurusan Kimia FMIPA UNMUL, 2018)
Synthesis of silica membrane from coal fly ash to decrease the color intensity of the liquid waste of sarung Samarinda industry has been done. The extraction of silica from coal fly ash by using the sol-gel process, and for silica membrane by using mixture of PVA (Poly Viny Acohol) and PEG (Polyethylen Glycol. Decrease in color intensity were analyzed using UV-Visible Spectrofotometer and the morphology of the membrane was observed by SEM-EDX. Based on the results from the spectrofotometer the concentration of the liquid waste berofe is 52.92 Unit Pt.Co and after decolorization is 25.04 Unit Pt.Co. The result show that decreasing are concentration is 52.68%, and the results the Scanning Electron Microscope (SEM)-EDX on the membrane after decolorization of liquid waste show distribution of pores in the membrane experiencing changes caused by new particles covering membrane be expected from liquid waste, and the elements are C, O, Na, Al and Si.